1998
DOI: 10.1007/s100510050497
|View full text |Cite
|
Sign up to set email alerts
|

First and second order transition in frustrated XY systems

Abstract: The nature of the phase transition for the XY stacked triangular antiferromagnet (STA) is a controversial subject at present. The field theoretical renormalization group (RG) in three dimensions predicts a first order transition. This prediction disagrees with Monte Carlo (MC) simulations which favor a new universality class or a tricritical transition. We simulate by the Monte Carlo method two models derived from the STA by imposing the constraint of local rigidity which should have the same critical behavior… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
94
1
12

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(114 citation statements)
references
References 56 publications
7
94
1
12
Order By: Relevance
“…Based on Monte Carlo data [3] and on a nonlinear sigma model [4], a tricritical scenario was favored. Others suggest a weakly first-order transition which becomes apparent only very close to the critical temperature T N , whereas further away from T N the data may be described by effective exponents [5][6][7]. An experimental indication for the latter scenario was found recently [8].…”
Section: (Received 30 May 2000)mentioning
confidence: 92%
“…Based on Monte Carlo data [3] and on a nonlinear sigma model [4], a tricritical scenario was favored. Others suggest a weakly first-order transition which becomes apparent only very close to the critical temperature T N , whereas further away from T N the data may be described by effective exponents [5][6][7]. An experimental indication for the latter scenario was found recently [8].…”
Section: (Received 30 May 2000)mentioning
confidence: 92%
“…[11] the results for the XY STA are interpreted as an evidence for mean-field tricritical behavior. Moreover, MC investigations [15] of special lattice spin systems, that on the basis of their symmetry should belong to the chiral universality class, show clearly a first-order transition.…”
mentioning
confidence: 99%
“…This may explain some experiments (for example those for the CsCuCl 3 compound, see, e.g., Refs. [5,6]) and MC studies for special lattice systems [15], where first-order transitions are observed. Beside the conventional critical exponents β, γ, ν, etc... related to the standard spin order, one may consider additional critical exponents related to the behavior of the chiral degrees of freedom.…”
mentioning
confidence: 99%
“…It is apparent from Fig.1 that the V L (T, p) value tends to 2/3 at L→∞. Such a behavior is, as has been mentioned above, typical for a second order transition [7]. Phase transition temperature T l (p) determined for all considered systems by the We calculate the static CE for the heat capacity , susceptibility , and order parameter β by means of the finite-size scaling theory (FSST).…”
Section: Results Of Simulationmentioning
confidence: 76%
“…This technique works well at detection of a transition order. One knows the distinctive features inherent in PT [7]: at a first order transition the averaged value V L (T, p) tends to some non-trivial value * V according to the equation…”
Section: Simulation Methodsmentioning
confidence: 99%